Cyberbullying Behavior Patterns in Adolescents in Jakarta - Endah Murwani; Helga Liliani Cakra Dewi (Ikatan Sarjana Komunikasi Indonesia, 2019)
This research is motivated by the phenomenon of cyberbullying in adolescents. Cyberbullying has the potential to harm victims such as loss of self-confidence, depression and decreased performance. Therefore, this study aims to determine the behavior patterns of cyberbullying perpetrators and victims of adolescents in Jakarta. Cyberbullying behavior patterns in this study refers to the concept of Willard which classifies seven behaviors: flaming, online harassment, denigration, impersonation, outing and trickery, exclusion, and cyberstalking. This research has been conducted with descriptive research, by taking high school students in DKI Jakarta as sample. A total of 400 students have been chosen by using multistage random sampling. Data was collected through a questionnaire and measured using the Student Assessment Survey (SAS). The results showed the involvement of students as perpetrators and victims of cyberbullying. Behavior that tends to be used by students as cyberbullying is denigration (77.2%), harassment (74%), and flaming (70%). While students who are victims of cyberbullying, the treatment that tends to be experienced is denigration (79.2%), flaming (78.7%) and harassment (75.2). The results of this study suggest the need for strategies to prevent cyberbullying behavior by literacy using social media effectively.